MoS2-based biosensor for SARS-CoV-2 detection: a numerical approach - Tene, Talia; Tubon-Usca, Gabriela; Gallegos, Katherine Tixi; Mendoza Salazar, María José; Vacacela Gomez, Cristian (Frontiers in Nanotechnology, 2025)
Surface plasmon resonance (SPR) biosensors are powerful tools for highly sensitive and specific detection of biomolecules. This study introduces a MoS₂-based SPR biosensor optimized for SARS-CoV-2 detection. The sensor integrates a multilayer configuration, including a BK7 prism, Ag film (45 nm), S₃N₄ layer (13 nm), MoS₂ monolayer (0.65 nm), and functionalized ssDNA layer (5 nm). Systematic optimization of each layer improved plasmonic coupling, propagation, and specificity, achieving a balance between sensitivity, resolution, and efficiency. The optimized biosensor was evaluated across virus concentrations ranging from 0.01 to 150 mM. The proposed biosensor demonstrated excellent performance at moderate to high concentrations, with sensitivity up to 261.33°/RIU, a quality factor of 36.16 RIU−1, and a limit of detection of 1.91 × 10−5. An optimal figure of merit of 405.50 RIU−1 was achieved at 10 mM, highlighting the sensor’s diagnostic potential. However, challenges remain at very low concentrations (0.01–0.1 mM), where angular shifts, sensitivity, and signal-to-noise ratio were negligible.